The Potential of Sea Pandan (Pandanus tectorius) Fiber as a Non-Food Industry Material Towards Sustainable Development - Meilisa, Nurmeilisa; Jumrodah, Jumrodah; Supriatin, Atin (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
Pandanus tectorius in certain areas has the potential to be utilized in the handicraft industry because it is known to have good and strong fiber. However, there are still many coastal areas in Indonesia that have not utilized P. tectorius optimally. The purpose of this study is to see the potential of P. tectorius fiber can be used as a non-food industry material towards sustainable development. The method used in this study is a laboratory experiment with a qualitative descriptive approach that uses different variations in NaOH concentrations, namely 0% (control), 2.5%, 5% and 7.5%. Research data was obtained from fiber tests in the laboratory which included fineness, tenacity, and elongation tests. The laboratory test results showed that P. tectorius fiber in NaOH treatment was 5% more optimal than NaOH treatment 0% (Control), 2.5% and 7.5% with an average fineness value of 2529.16 Tex, an extended value of 15.11%, a tenacity value of 153.71 (mN/Tex) and 15.68 (gf/Tex). Based on the results of the analysis, it is known that P. tectorius has good characteristics used as a non-food industry material, so that by utilizing the potential of P. tectorius fiber is a creative industry towards sustainable development